The Impact of Exacerbation Frequency on Clinical and Economic Outcomes in Swedish COPD Patients: The ARCTIC Study - Larsson,Kjell; Janson,Christer; Lisspers,Karin; StÃ¤llberg,BjÃ¶rn; Johansson,Gunnar; Gutzwiller,Florian S; Mezzi,Karen; Bjerregaard,Bine Kjoeller; Jorgensen,Leif (International Journal of Chronic Obstructive Pulmonary Disease, 2021)
Kjell Larsson,1 Christer Janson,2 Karin Lisspers,3 Björn Ställberg,3 Gunnar Johansson,3 Florian S Gutzwiller,4 Karen Mezzi,4 Bine Kjoeller Bjerregaard,5 Leif Jorgensen5 1Integrative Toxicology, The National Institute of Environmental Medicine, Karolinska Institute, Stockholm, Sweden; 2Department of Medical Sciences: Respiratory, Allergy and Sleep Research, Uppsala University, Uppsala, Sweden; 3Department of Public Health and Caring Sciences, Family Medicine and Preventive Medicine, Uppsala University, Uppsala, Sweden; 4Novartis Pharma AG, Global Patient Access, Basel, Switzerland; 5IQVIA Solutions, Real World Evidence Solutions, Copenhagen, DenmarkCorrespondence: Kjell LarssonIntegrative Toxicology, The National Institute of Environmental Medicine, Karolinska Institute, Stockholm, SE-171 77, SwedenTel +467 0582 0763Email kjell.larsson@ki.sePurpose: The aim of this study was to assess the association between exacerbation frequency and clinical and economic outcomes in patients with COPD.Patients and Methods: Electronic medical record data linked to National Health Registries were collected from COPD patients at 52 Swedish primary care centers (2000– 2014). The outcomes analyzed were exacerbation rate, mortality, COPD treatments, lung function and healthcare costs during the follow-up period. Based on the exacerbation rate two years before index date, the patients were initially classified into three groups, either 0, 1 or ≥ 2 exacerbations per year. After the index date, the classification into exacerbation groups was updated each year based on the exacerbation rate during the last year of follow-up. A sensitivity analysis was conducted excluding patients with asthma diagnosis from the analysis.Results: In total 18,586 COPD patients were analyzed. A majority of the patients (60– 70%) who either have had no exacerbation or frequent exacerbations (≥ 2/year) during the pre-index period remained in their group (ie, with 0 or ≥ 2 annual exacerbations) during up to 11 years of follow-up. Compared with having no ...